ARTIFICIAL INTELLIGENCE (AI): PRACTICES AND PROBLEMS EXPERIENCED BY INTERIOR DESIGNERS - Mehta, Mona; Shah, Himani; Dasgupta, Rakhi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The development of artificial intelligence (AI) has swept the globe. Tools of artificial intelligence are now readily available to everyone due to the advancement of new and more refined AI every day, and they carry the potential to fundamentally alter the way one lives, works, and interacts with their surroundings. The interior design strategy based on artificial intelligence technology is being used to optimize the entire interior design work to increase technological innovation in space. Designers can input their preferences and design ideas into artificial intelligence systems for interior design and receive suggestions for furniture, colour palettes, and other design elements. These AI applications are helpful to optimize the work management of an interior designer as well as appease the clients. The main aim of the research study is to find out the practices and problems experienced by Interior designers regarding the applications of artificial intelligence in professionally managing and completing interior design projects. Data was collected from 80 respondents using a questionnaire through the purposive sampling method. The results of this investigation were valuable for Interior Design professionals, to get refined knowledge about the development of Artificial Intelligence tools used in professional management of Interior Design. Through this study various informative programmes can be conducted about the latest trends in Artificial Intelligence technology, its use and applicability.